Effect of Additional Cellulose Bacterial from Nata De Soya and Chitosan in Bioplastic Manufacturing - Nelvira Juanmara Ardyansa; Ari Suwito Putra Ramadhon; Sintha Soraya Santi (Journal of Applied Science, Engineering, Technology, and Education, 2022)
Plastics are synthetic polymers from petroleum or petrochemicals that are difficult to biodegrade by bacteria and microbes. Non-biodegradable plastics cause the accumulation of large amounts of plastic waste Solutions that can reduce plastic waste by making plastics that are easily biodegradable. In this study, tofu liquid waste is used as a basic material for the manufacture of bioplastics. Tofu liquid waste is waste generated from tofu production. This study aims to determine the effect of adding bacterial cellulose and chitosan on the manufacture of bioplastics from liquid waste tofu (whey) in terms of tensile strength, elongation, water solubility, and functional groups (FTIR) in accordance with PET plastic standards (Polyethylene terephthalate). The research procedure on the effect of adding bacterial cellulose and chitosan on the bioplastic fabrication of Nata De Soya. First, from tofu liquid waste, Acetobacter Xylinum starter was added and then fermented for 10-12 days to become Nata De Soya. After that it was neutralized with aquadest, removed the water by pressing, and dried to become bacterial cellulose. The process of making bioplastic with the addition of chitosan (grams) 2,3; 3.1; 3.9; 4.7 and 5.5 and bacterial cellulose (grams) 0.5 ;1.5; 3.9; 7; and 11. In the manufacture of bioplastics with the addition of Bacterial Cellulose and chitosan, it is appropriate, namely the tensile strength obtained will increase and the solubility in water decreases. From the results of our research, the best results were obtained in the addition of S5K5 with a tensile strength value of 9.665 MPa, an elongation value of 31.3%, and a solubility value in water of 17.9%. It has a higher tensile strength, smaller elongation and lower water solubility. The effect of the addition of chitosan on the tensile strength value can increase the tensile strength (Tensile Strength Value), the addition of bacterial bacterial cellulose and chitosan can affect the elongation of bioplastics getting smaller and the effect of chitosan can reduce solubility in water. It is good but still far from the standard PET (Polyethylene Terefelat) which is 60-80 Mpa.